Épopée, guerre coloniale et communauté politique dans le vice-royaume du Pérou, 1560-1610 - Choi, I (L'Ouvroir Litt&Arts, 2018)
This article presents a partial overview of my doctoral thesis, written under the supervision of Rodrigo Cacho at the University of Cambridge, UK, and defended in 2017. It explores the relationship between colonial warfare and the body politic in the Viceroyalty of Peru through an analysis of three poems : Alonso de Ercilla’s La Araucana (1569-89), Pedro de Oña’s Arauco domado (1596) and Juan de Miramontes Zuázola’s Armas antárticas (c. 1608-09). I argue that the representation of the diverse political communities which feature in these poems – indigenous peoples, Spanish colonists, the Ottoman empire and African maroon settlements among others – is central to the structure of these epics and has been almost completely neglected. The just conduct of violent conflicts between and within these communities depends in large measure on the status accorded to the adversary, which is precisley what these poems problematise, playing on the reader’s expectations in order to open them to question. The resulting vision demonstrates how the ‘connected histories’ of Iberian early modernity had a decisive impact on the political and literary imagination.